PENGARUH FAKTOR SOSIAL, BUDAYA DAN RELIGIUSITAS TERHADAP KEPUTUSAN ANGGOTA MENABUNG DI BMT UGT SIDOGIRI CAPEM SEMPU - Ribut Suprapto; Nawal Ika Susanti; Zulfi Ferikha (JPSDa: Jurnal Perbankan Syariah Darussalam, 2022)
This research is motivated by the competitive conditions of Islamic microfinance institutions, especially in BMTs which are getting tighter from time to time, so that each BMT must create a new marketing strategy in order to maintain and achieve a wider market share and can increase member satisfaction, namely with social factors. , culture, and religiosity. The purpose of this study was to determine the effect of social, cultural and religiosity factors on members' decisions to save at BMT UGT Sidogiri Capem Sempu and to determine the econometric model of the problem. In this study using a quantitative approach. Hypothesis testing using t-test and f-test shows that: (1) social variables have a significant effect on members' decisions to save at BMT UGT Sidogiri Capem Sempu. (2) The cultural variable has no significant effect on members' decisions to save at BMT UGT Sidogiri Capem Sempu. (3) The religiosity variable has a significant effect on members' decisions to save at BMT UGT Sidogiri Capem Sempu. Social, cultural and religious factors have an influence of 20.1% on members' decisions to save at BMT UGT Sidogiri Capem Sempu while the remaining 70.9% is influenced by other variables not explained in this study.